A new species of manakin (Aves: Pipridae; Machaeropterus) from Peru with a taxonomic reassessment of the Striped Manakin (M. regulus) complex - Lane, Daniel F.; Kratter, Andrew W.; O’neill, John P. (Zootaxa, 2017)
We describe a new taxon of manakin in the Machaeropterus regulus complex, from the foothills of southwestern Loreto and northern San Martín departments, Peru. This new form appears to be almost identical morphologically to the Tepui form M. regulus aureopectus but differs strongly from that and all other members of the M. regulus complex in voice. Therefore, we conclude that this population represents a new biological species that we here name Machaeropterus eckelberryi. Based on voice and some morphological characters, we concur with several previous authors (e.g., Whittaker & Oren 1999; Snow 2004; Ridgely & Tudor 2009) that nominate M. regulus (Eastern Striped Manakin), of the Atlantic Forest of Brazil, should be separated as a biological species from the polytypic Machaeropterus striolatus of western South America (Western Striped Manakin), including M. s. striolatus of Amazonia, M. r. obscurostriatus and M. r. zulianus of the Venezuelan Andes, M. r. antioquiae of the Colombian Andes, and M. r. aureopectus of the tepuis region.